A method of determining multi-wavelength lidar ratios combining aerodynamic particle sizer spectrometer and sun-photometer. (September 2018) - Zhao, Hu; Mao, Jiandong; Zhou, Chunyan; Gong, Xin
Highlights: A practical method makes use of aerodynamic particle sizer spectrometer and sunphotometer to determine the multi-wavelength lidar ratios is proposed. The difficulty in the determination of lidar ratios in multi-wavelength lidar is overcome. The inversion precision of aerosol optical parameters of multi-wavelength lidar is improved. This method realizes real-time inversion of multi-wavelength lidar data. Abstract: The lidar equation solution for atmosphere requires knowledge of the lidar ratio along the lidar line of sight. The lidar ratio is depended on the wavelength of lidar, so it is difficult to determine the lidar ratios in multi-wavelength lidar. A method that determines the multi-wavelength lidar ratios combining sun-photometer and aerodynamic particle sizer spectrometer (APS) is proposed. The optimal lidar ratios at three wavelengths (355 nm, 532 nm and 1064 nm) are deduced from comparing the aerosol optical depth (AOD) derived from sun-photometer and the multi-wavelength lidar. The feasibility and practicability of this method is tested by the actual experiment. The uncertainty of determining lidar ratios in multi-wavelength lidar is reduced. The aerosol extinction coefficient retrieved using this method is improved with accuracy of 12.8%, 26.3% and 8.2% at 355 nm, 532 nm and 1064 nm respectively.